Improved Direct Power Control of T-Type Rectifiers With Parameter Robustness Feedforward Compensation for DC-Bus Voltage Ripple Suppression Under Unbalanced Grid Conditions - Yi-Hung Liao; Jia-Sheng Liu; Pu-Yi Huang; Ping-Ju Chen (IEEE Open Journal of the Industrial Electronics Society)
In a three-phase three-level ac/dc converter, the T-type rectifier features high efficiency and lower power switch stress, and it allows the dc-side voltage to serve as two independent output voltage sources. In practical applications, the operation of the T-type rectifier under unbalanced three-phase grid conditions must be considered. This article establishes an improved direct power control structure based on extended power theory under unbalanced grid conditions to achieve distortion-free current for the T-type rectifier. Additionally, a feedforward virtual capacitor power compensation is created to eliminate the output voltage ripples caused by the ripple power of the rectifier inductance under the unbalanced three-phase grid. The controller design of the improved direct power control and the choice of the virtual capacitor are analyzed. Furthermore, the proposed method regulates the neutral point voltage of the T-type rectifier, eliminates neutral point current disturbances, and provides a stable and accurate dc output voltage, ensuring high quality power supply. The proposed strategy does not require a phase-locked loop or ac-side system parameters, resulting in excellent dynamic performance and robustness against parameter mismatches. Finally, the effectiveness and feasibility of the proposed control strategy are verified through simulation results and the implementation of a 2.4 kW three-phase T-type rectifier.